DETECTION OF MYCOBACTERIAL LOAD AND LOCATION OF PERSISTING AFB IN CASES OF NON RESPONDERS ON CONVENTIONAL ANTITUBERCULOSIS DRUGS; A HISTOMORPHOLOGICAL STUDY: Responders of Conventional Antituberculosis Drugs - Zubair, Dr Alia; Jamal, Shahid; Mubarik, Azhar; Saeed, Waseem (Pakistan Armed Forces Medical Journal, 2012)
Objective: To examine the patterns of infection in terms of tissue pathology, bacillary load and bacterial location seen in non responders to routine antituberculosis drugs. Design: Cross sectional descriptive study Place and duration: Department of Histopathology, Army Medical College Rawalpindi, National University of Sciences & Technology (NUST) Islamabad, and Military Hospital Rawalpindi, Pakistan from October 2009 to February 2011. Patients and Methods: The patients receiving supervised multidrug therapy for tuberculosis and revealing evidence of tuberculosis on microscopic examination were included in the study. The tissue pathology on H&E staining was categorized as mild, moderate or severe. Histomorphological patterns for all granulomas were also assessed. Ziehl-Neelsen (ZN) stain was used to visualize acid fast bacilli. Results: Twenty nine cases examined comprised of 16 lung biopsies and 13 extrapulmonary tissues. Mild inflammation was found in 14 (48.3%) cases out of 29 while 11 (37.9%) cases exhibited moderate and 4 (13.8%) cases severe pathology. Large coalescing granulomas were found in 17 (58.6%), multifocal lesions in 9 (31.0%), and necrotic granulomas in 9 (31.0%) cases. Regarding cellular composition of granulomas, 23 (79.3%) cases revealed lymphocytic cuff while giant cells were seen in 55.2% of cases. Three cases (10.3%) had foamy macrophages. On ZN stain, scanty AFB were seen predominantly (48.3%) within necrotic area of the granulomatous tissue. Conclusion: The TB cases resistant to conventional antimycobacterial drugs show distinct tissue pathology. The findings highlight mild to moderate chronic inflammatory changes in the form of large coalescing granulomas with few persisting mycobacterium mainly within the necrotic foci of granulomatous tissue.